Teenagers' health concerns: implications for primary health care professionals. - Epstein, R (1989)
Four hundred and eighty five students, aged 13-15 years, at nine comprehensive schools in the London borough of Brent completed a questionnaire about health-related behaviours and health concerns. Among general health concerns, most prominent were weight, acne, nutrition and exercise. There appeared to be a considerable unmet need to discuss sexual development, sexually transmitted diseases and contraception. A substantial proportion (16% of the girls and 3% of the boys) reported sexual abuse, but few wished to discuss this with a doctor or nurse. Although a relatively high percentage of the students smoked and a smaller percentage used alcohol or drugs regularly, there was little concern or interest in discussing these matters with a health professional. Most of the schools did not have a formal health education programme, and in none of them were health professionals available for discussion of the issues under study. There appears to be a need for more comprehensive health education in schools and for primary health care professionals, particularly general practitioners to raise these issues opportunistically with their teenage patients.